Environmental Impact Assessment of LED Lamp Types for Industrial Lighting Purpose - Gunawardhana, Lakshani; Karunanayake, Nalan; Amarasiri, Chamali (Science & Technology Asia, 2023)
Thailand aims to cut final energy consumption to 30% of the 2010 level by 2037 via the National Energy Efficiency Plan (2018 - 2037). The plan focuses on promoting LED lighting and enhancing energy efficiency in the industrial sector. Thai authorities are working on longterm strategies for effective energy and environmental management. It’s important to avoid using residential LED lamps in industrial facilities to prevent energy wastage and environmental degradation. This study used Life Cycle Assessment (LCA) to evaluate the environmental impact of using the wrong LED lamp type in industrial lighting. It also examined how Thailand's current (2023), and future (2036) electricity mix affects environmental impact. The findings revealed that using residential LED lamps for industrial purposes results in a 25% higher environmental impact during the usage phase. The higher environmental impact during the usage phase is mainly caused by the lower efficiency of residential LED lamps. The sensitivity analysis found that the 2023 electricity mix has a more significant impact on 10 midpoint impact categories than the 2036 mix. Notably, ionizing radiation and water consumption were significantly affected by the 2036 electricity mix. However, at the endpoint level, the 2036 electricity mix had lower environmental impacts compared to the 2023 mix. Choosing the right LED lamp for industrial lighting is crucial to reduce energy waste and limit environmental harm. Furthermore, when planning for future clean energy generation, it's important to factor in the impact of the electricity mix.